(untitled) (Research, Society and Development, 2021)
Objective: To analyze the epidemiological profile of tuberculosis in the state of Pernambuco in the last 10 years. Methodology: This is a descriptive, retrospective and quantitative study of tuberculosis cases in the state of Pernambuco from 2009 to 2019. The elements used are secondary to the Information System and Notifiable Diseases (SINAN) found through the Department of Informatics of the Unified Health System (DATASUS). Results: In the last 10 years, 61,449 cases of tuberculosis were reported in the state of Pernambuco. When analyzing the profile of confirmed cases, it was found that 70% are male, the age group 20 to 39 years old prevailed with 28,458 reported cases. The most prevalent clinical form of tuberculosis in the pulmonary period, with 52,242 reported cases. Conclusion: The results found in the present study show that in Pernambuco there was a prevalence of tuberculosis in men of reproductive age and with low education. Tuberculosis remains a serious public health problem in the State of Pernambuco. Therefore, direct and indirect actions aimed at preventing tuberculosis, in different areas of health regions. In this sense, understanding the epidemiological dynamics of tuberculosis becomes a priority for the inclusion of health education offers due to the lack of information such as the risk factors related to the pathology in order to avoid infection in the state of Pernambuco.